Potensi Antibakteri Phyllanthus niruri terhadap Bakteri Gram-Positif: Systematic Literature Review tentang Senyawa Bioaktif dan Mekanisme Molekuler - Nur Haslinar Hasan; Hamidah Samad; Yusminah Hala (Mataram University, 2026)
Antimicrobial resistance has become a major global health challenge that threatens the effectiveness of existing antibiotic therapies. The rapid emergence of multidrug-resistant bacteria highlights the urgent need for alternative antibacterial agents, including those derived from medicinal plants. This study aimed to evaluate the antibacterial potential of Phyllanthus niruri against Gram-positive bacteria and to identify the bioactive compounds and possible molecular mechanisms involved. A systematic literature review was conducted following the PRISMA 2020 guidelines. Articles were retrieved from the Scopus database using the keywords “Phyllanthus niruri” and “antibacterial” or “antimicrobial”. After applying predefined inclusion and exclusion criteria, 15 studies published between 2021 and early 2026 were included in the analysis. The results indicate that P. niruri consistently exhibits antibacterial activity against several Gram-positive bacteria, particularly Staphylococcus aureus. Antibacterial activity was commonly evaluated using inhibition zone assays, minimum inhibitory concentration, and minimum bactericidal concentration tests. Several bioactive compounds, including flavonoids, tannins, alkaloids, and lignans such as phyllanthin, were identified as contributors to antibacterial activity. These compounds may inhibit essential bacterial proteins such as DNA gyrase and penicillin-binding proteins and disrupt bacterial cell membranes. Overall, P. niruri shows promise as a natural source of antibacterial agents against Gram-positive bacterial infections.